The way of acting : the theatre writings of Tadashi Suzuki - Suzuki, Tadashi, 1939- (Theatre Communications Group, 2014)
Although Tadashi Suzuki has long been considered one of the world's foremost contemporary theatre artists, until now his writings have been unavailable in English. This landmark collection provides a useful, provocative introduction to Suzuki's philosophical as well as practical approaches to the stage, offering Western audiences long overdue insight into Suzuki's singular artistry.